Capillary flow in microchannel circuitry of scleral lenses. Issue 20 (9th April 2019) - Yetisen, Ali K.; Soylemezoglu, Bugra; Dong, Jie; Montelongo, Yunuen; Butt, Haider; Jakobi, Martin; Koch, Alexander W.
Abstract : Simple and complex microchannels are formed in scleral lenses using laser pattering to perform microfluidic operations via capillary action. Abstract : Continuous monitoring of biomarkers in a quantitative manner at point-of-care settings can advance early diagnosis in medicine. Contact lenses offer a minimally-invasive platform to continuously detect biomarkers in tear fluid. Microfluidic components as lab-on-a-chip technology have the potential to transform contact lenses into fully-integrated multiplexed sensing devices. Here, simple and complex microchannels are created in scleral lenses that perform microfluidic operations via capillary action. The engraving of microchannels in scleral lenses were performed by laser micromilling, where a predictive computational model was developed to simulate the effect of laser power and exposure time on polymer behavior. Experimentally varying the CO2 laser power (1.2–3.6 W) and speed (38–100 mm s −1 ) allowed the micromilling of concave microchannels with groove depths of 10–240 μm and widths of 35–245 μm on polymetric substrates. The demonstrated laser micromilled circuitry in scleral lenses included linear channels, T/Y junctions, multiplexed arrays, mixers, and spiral channels, as well as serially organized multicomponent channels. Capillary forces acting in the microchannels allowed flowing rhodamine dye within the microfluidic components, which was visualized by optical microscopy in reflection and transmission modes simultaneously. The developed microfluidic components in scleral lenses may enable tear sampling, storage, analysis, and multiplexed detection capabilities for continuous monitoring applications.